One uncommon bis-sesquiterpenoid from Xisha soft coral Litophyton nigrum. (5th January 2022) - Yang, Fan; Hua, Qiang; Yao, Li-Gong; Liang, Lin-Fu; Lou, Yu-Xia; Lu, Yan-Hua; An, Fa-Liang; Guo, Yue-Wei
Graphical abstract: Abstract: One uncommon sesquiterpenoid dimer (1 ), a new nardosinane-type sesquiterpenoid (3 ), along with two known sesquiterpenoids (2 and 4 ) were isolated from soft coral Litophyton nigrum using a structure-oriented HR-MS/MS approach. The configurations of the isolates were determined by spectroscopic data analyses, including HR-ESI-MS, 1D/2D NMR, single crystal X-ray diffraction, and DP4+ statistical analyses. Compound 3 exhibited potent PTP1B inhibitory activity (IC50  = 10.67 ± 1.81 μg/mL) compared to the positive control.